PP.12.06: DIFFERENT PATTERNS OF BEAT TO BEAT VENTRICULAR-ARTERIAL INTERACTIONS IN YOUNG MEN. (June 2015) - Gonzalez, S.; Kempny, P.; Castellaro, C.; Forcada, P.; Svane, J. Chiabaut; Inserra, F.; Casarini, M.; Obregon, S.; Hita, A.; Kotliar, C.
Abstract : Objective: Recently anterograde influences of left ventricular contractility over arterial stiffness have been evidenced in young men in population studies. However, is possible that different patterns of cardiovascular adjustment could be recognized through beat-to-beat measurements. a- To describe beat-to-beat relationships between left ventricular function and aortic stiffness (anterograde (AI) and retrograde (RI) interactions), in normotensive and hypertensive patients. b- Correlate these profiles with the autonomic modulation. Design and method: Of 130 patients evaluated, and after exclusion criteria (female, age < 18 > 60 years, secondary hypertension, diabetes, kidney disease, cardiovascular event, and sympatholytics) 22 males were included: 11normotensives (40.8 ± 9.8 years, 126.1 ± 8.6/81.1 ± 8.0 mm Hg) and 11mild hypertensive patients (42.1 ± 10.2 years, 137.2 ± 15.1/89.3 ± 9.0 mm Hg) treated with RAAS-blockers. BP (ESH), HR, ejection time (ET) and dZ/dT(a dV/dT estimator) were determined by impedance cardiography, together with tonometric carotid-femoral PWV; all the measurements were performed beat-to-beat, for 3 minutes at rest. Both sets of determinations were coordinated through R-R intervals. Spectral analysis of parasympathetic (HF, ms2)/sympathetic (LF/HF) and overall autonomic modulation (total power, TP, ms2) were performed through heart rate variability during 3 minutes/lying. Aortic augmentation index at 75bpm (AIX75) was measured. Beat-to-beat correlations between dZ/dT and ET with PWV were performed, identifying positive/negative signs of the interactions (AI/RI, respectively), (Pearson). We assessed differences between autonomic modulation and AIX75 according to AI/RI (T-test). Results: Significant beat-to-beat correlations between dZ/dT and PWV were evident: Type-AI in 59% (n = 13; r = from 0.22 to 0.71, p < 0.05) and Type-RI in the remaining 41% (n = 9; r = -0.22 to -0.72, p < 0.05). ET was not significantly associated with PWV (p > 0.05). AI/RI prevalence were similar between normotensive and hypertensive patients (chi2, p = 0.96). LF/HF was similar between AI/RI (p = 0.87). HF and TP were higher in AI subjects (409 vs. 112 ms2 and 1007 vs. 418 ms2, respectively; p < 0.05). AIX75 was higher in RI subjects (20.8 vs.7.3%, p < 0.002). Figure. No caption available. Conclusions: Two beat-to-beat ventricular-arterial interaction types in young men were noted. The anterograde interaction pattern appears to be more physiological, presenting greater parasympathetic and overall autonomic modulations, and less aortic reflections, which could have a lesser impact on target organ damage development.